Associations between the prevalence of influenza vaccination and patient's knowledge about antibiotics. (December 2015) - Hoffmann, Kathryn; van Bijnen, Evelien; George, Aaron; Kutalek, Ruth; Jirovsky, Elena; Wojczewski, Silvia; Maier, Manfred
Abstract Background This study aimed to identify associations between GP patient's knowledge about the spectrum of effectiveness of antibiotics and the probability of vaccination against influenza. The underlying hypothesis was that individuals with an understanding that antibiotics are ineffective against viruses, common colds, and flu were more likely to be vaccinated than persons lacking this knowledge. Methods This cross-sectional study was conducted within the context of the European APRES project in Austria. Between November 2010 and July 2011, patients were recruited from GP practices to complete questionnaires about their knowledge about antibiotics and their influenza vaccination status. Statistical analyses included subgroup analyses and logistic regression models. Results Data of 3224 patients was analyzed, demonstrating that patients with better knowledge concerning antibiotics had a significantly higher likelihood of being vaccinated (OR 1.35, CI 95 % 1.18–1.54). While the overall vaccination rate was low (18.6 % in 2009/2010 and 14.0 % in 2010/2011), elderly compared to younger adults (OR 0.06 CI 95 % 0.03–0.13) and healthcare workers (OR 2.24, CI 95 % 1.42–3.54) demonstrated higher likelihood of vaccination. Additionally, female GPs had significantly more vaccinated patients than male GPs (OR 2.90, CI 95 % 1.32–6.40). Discussion There has been little prior study on the association between a patient's knowledge of the effectiveness spectrum of antibiotics and influenza vaccination status. Given the public health imperative to increase annual prevalence of influenza vaccination, understanding this educational gap can improve specificity in counseling as well as vaccination rates. Ultimately, we found that those with a better knowledge on about antibiotics had a significantly higher likelihood of being vaccinated. Conclusions The results of this study demonstrate that vaccination prevalence is associated with patient's knowledge about antibiotics. It can be concluded that one strategy to improve the overall low vaccination rates for seasonal influenza in Austria would be, particularly for male GPs, to have a specific discussion with patients about these circumstances by focusing on younger patients. Further, public health efforts could supplement in-office strategies to improve this area of health literacy.